2000
DOI: 10.1007/s000180050045
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol inhibits tumor necrosis factor- ? -induced nuclear factor kappa B activation and adhesion molecule expression in human vascular endothelial cells

Abstract: The transcriptional regulatory protein nuclear factor kappa B (NF-kappa B) participates in the control of gene expression of many modulators of inflammatory and immune responses, including vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1). The heightened expression of these adhesion molecules has been reported to play a critical role in atherosclerosis, inflammation, ischemic vascular disorders, diabetes, and cancer metastasis. In the present study, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 34 publications
(50 reference statements)
1
78
0
Order By: Relevance
“…The lower band could represent inactivated NFkB bound with IB or the monomeric p52 component of NFkB. 35) Incubation of genistein at 20-100 mM with cells did not show inhibitive eŠect on NFkB activity in dose-dependent manner. Genistein at 50 mM and 100 mM inhibited the activation of NFkB induced by LPS signiˆcantly (Fig.…”
Section: Fig 3 Ešects Of Genistein On Gsh Concentration In Lps-mentioning
confidence: 85%
“…The lower band could represent inactivated NFkB bound with IB or the monomeric p52 component of NFkB. 35) Incubation of genistein at 20-100 mM with cells did not show inhibitive eŠect on NFkB activity in dose-dependent manner. Genistein at 50 mM and 100 mM inhibited the activation of NFkB induced by LPS signiˆcantly (Fig.…”
Section: Fig 3 Ešects Of Genistein On Gsh Concentration In Lps-mentioning
confidence: 85%
“…PYC is a mixture of phenols, polyphenols, taxifolin, and condensed flavonoids (40), and it is known that it has a strong antioxidant effect (38). Nowadays, PYC is widely used in general populations as a dietary supplement beneficial for various conditions despite the lack of sufficient knowledge about the molecular basis of its action.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling occurs via an oxidant-sensitive pathway (21)(22)(23)(24)(25). Our previous studies showed that the endothelial cell is a key target of PMN NADPH oxidase activity (26 Interactions of polymorphonuclear neutrophils (PMNs) with endothelial cells may contribute to the activation of endothelial cell responses involved in innate immunity.…”
Section: Introductionmentioning
confidence: 99%